Optimal. Leaf size=23 \[ -2+\frac {4 x}{e}+e^{-2-2 x} x (2 x+\log (x)) \]
________________________________________________________________________________________
Rubi [A] time = 0.55, antiderivative size = 30, normalized size of antiderivative = 1.30, number of steps used = 18, number of rules used = 8, integrand size = 39, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.205, Rules used = {6741, 6742, 2194, 2176, 2554, 12, 2178, 2199} \begin {gather*} 2 e^{-2 x-2} x^2+\frac {4 x}{e}+e^{-2 x-2} x \log (x) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 2176
Rule 2178
Rule 2194
Rule 2199
Rule 2554
Rule 6741
Rule 6742
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int e^{-2-2 x} \left (1+4 e^{1+2 x}+4 x-4 x^2+\log (x)-2 x \log (x)\right ) \, dx\\ &=\int \left (\frac {4}{e}+e^{-2-2 x}+4 e^{-2-2 x} x-4 e^{-2-2 x} x^2+e^{-2-2 x} \log (x)-2 e^{-2-2 x} x \log (x)\right ) \, dx\\ &=\frac {4 x}{e}-2 \int e^{-2-2 x} x \log (x) \, dx+4 \int e^{-2-2 x} x \, dx-4 \int e^{-2-2 x} x^2 \, dx+\int e^{-2-2 x} \, dx+\int e^{-2-2 x} \log (x) \, dx\\ &=-\frac {1}{2} e^{-2-2 x}+\frac {4 x}{e}-2 e^{-2-2 x} x+2 e^{-2-2 x} x^2+e^{-2-2 x} x \log (x)+2 \int e^{-2-2 x} \, dx+2 \int \frac {e^{-2-2 x} (-1-2 x)}{4 x} \, dx-4 \int e^{-2-2 x} x \, dx-\int -\frac {e^{-2-2 x}}{2 x} \, dx\\ &=-\frac {3}{2} e^{-2-2 x}+\frac {4 x}{e}+2 e^{-2-2 x} x^2+e^{-2-2 x} x \log (x)+\frac {1}{2} \int \frac {e^{-2-2 x}}{x} \, dx+\frac {1}{2} \int \frac {e^{-2-2 x} (-1-2 x)}{x} \, dx-2 \int e^{-2-2 x} \, dx\\ &=-\frac {1}{2} e^{-2-2 x}+\frac {4 x}{e}+2 e^{-2-2 x} x^2+\frac {\text {Ei}(-2 x)}{2 e^2}+e^{-2-2 x} x \log (x)+\frac {1}{2} \int \left (-2 e^{-2-2 x}-\frac {e^{-2-2 x}}{x}\right ) \, dx\\ &=-\frac {1}{2} e^{-2-2 x}+\frac {4 x}{e}+2 e^{-2-2 x} x^2+\frac {\text {Ei}(-2 x)}{2 e^2}+e^{-2-2 x} x \log (x)-\frac {1}{2} \int \frac {e^{-2-2 x}}{x} \, dx-\int e^{-2-2 x} \, dx\\ &=\frac {4 x}{e}+2 e^{-2-2 x} x^2+e^{-2-2 x} x \log (x)\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.30, size = 24, normalized size = 1.04 \begin {gather*} e^{-2 (1+x)} x \left (4 e^{1+2 x}+2 x+\log (x)\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.45, size = 30, normalized size = 1.30 \begin {gather*} {\left (2 \, x^{2} e + x e \log \relax (x) + 4 \, x e^{\left (2 \, x + 2\right )}\right )} e^{\left (-2 \, x - 3\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.13, size = 30, normalized size = 1.30 \begin {gather*} {\left (2 \, x^{2} e^{\left (-2 \, x + 1\right )} + x e^{\left (-2 \, x + 1\right )} \log \relax (x) + 4 \, x e^{2}\right )} e^{\left (-3\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.14, size = 31, normalized size = 1.35
method | result | size |
default | \({\mathrm e}^{-1} \left (4 x +\left (x \,{\mathrm e} \ln \relax (x )+2 x^{2} {\mathrm e}\right ) {\mathrm e}^{-2 x -2}\right )\) | \(31\) |
norman | \(\left (x \ln \relax (x )+2 x^{2}+4 x \,{\mathrm e}^{-1} {\mathrm e}^{2 x +2}\right ) {\mathrm e}^{-2 x -2}\) | \(31\) |
risch | \(x \,{\mathrm e}^{-2 x -2} \ln \relax (x )+2 \left (x \,{\mathrm e}+2 \,{\mathrm e}^{2 x +2}\right ) x \,{\mathrm e}^{-2 x -3}\) | \(34\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} \frac {1}{2} \, {\left (2 \, x + 1\right )} e^{\left (-2 \, x - 2\right )} \log \relax (x) + 4 \, x e^{\left (-1\right )} + \frac {1}{2} \, {\rm Ei}\left (-2 \, x\right ) e^{\left (-2\right )} + {\left (2 \, x^{2} + 2 \, x + 1\right )} e^{\left (-2 \, x - 2\right )} - {\left (2 \, x + 1\right )} e^{\left (-2 \, x - 2\right )} - \frac {1}{2} \, e^{\left (-2 \, x - 2\right )} \log \relax (x) - \frac {1}{2} \, e^{\left (-2 \, x - 2\right )} - \frac {1}{2} \, \int \frac {{\left (2 \, x + 1\right )} e^{\left (-2 \, x - 2\right )}}{x}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 4.14, size = 27, normalized size = 1.17 \begin {gather*} 4\,x\,{\mathrm {e}}^{-1}+2\,x^2\,{\mathrm {e}}^{-2\,x-2}+x\,{\mathrm {e}}^{-2\,x-2}\,\ln \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.32, size = 24, normalized size = 1.04 \begin {gather*} \frac {4 x}{e} + \left (2 x^{2} + x \log {\relax (x )}\right ) e^{- 2 x - 2} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________